STRATEGI PENGELOLAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP NEGERI 02 JENGGAWAH - AGUSTIN, SITI ZULFA (Pendidikan Islam Pascasarjana IAIN Jember, 2018)
The strategy of learning is really needen either for teachers or students. For the teachers, the strategy can be the guidelines and references to implement the learning systematically. For the students, the usage of learning strategy can facilitate the learning process and hasten the understanding of the lesson, because every strategy is composed to make the learning process much easier. The learning processof learning management strategyis very important role in order to help the teachers in delivering the learning material to the students. The strategy of learning management is a way to organize the student’s interaction with the variables methods which can lead to a conducive, effective and efficient learning process.